Determinan Pengungkapan Corporate Social Responsibility - Nathaniel Archel Tiwow; Nicken Destriana (Media Bisnis, 2022)
The purpose of this research is to obtain empirical evidence about the factors that affect corporate social responsibility disclosure. This research determines whether there is an effect of media exposure, taxes aggressiveness, institutional ownership, managerial ownership, independent board, the board size, and profitability on corporate social responsibility disclosure. The objects of this research are manufacturing firms listed on Indonesia Stock Exchange (IDX) during the research period 2018-2020. The samples are chosen by using purposive sampling methods. There are 42 companies that met the criteria used in this research. The research model is analyzed by using multiple regression. Corporate social responsibility disclosure as the dependent variable using the 78-items index provided by Sembiring (2005). The result of this research shows that independent board and board size have a positive effect on corporate social responsibility disclosure. The presence of the board of commissioners in the company can increase the power of supervision to be able to provide pressure/encouragement to management in improving the quality of disclosure of company information and ensuring that CSR activities are carried out by the company.